2022
DOI: 10.1161/circoutcomes.121.008612
|View full text |Cite
|
Sign up to set email alerts
|

County-Level Social Vulnerability is Associated With In-Hospital Death and Major Adverse Cardiovascular Events in Patients Hospitalized With COVID-19: An Analysis of the American Heart Association COVID-19 Cardiovascular Disease Registry

Abstract: Background: The COVID-19 pandemic has disproportionately affected low-income and racial/ethnic minority populations in the United States. However, it is unknown whether hospitalized patients with COVID-19 from socially vulnerable communities experience higher rates of death and/or major adverse cardiovascular events (MACEs). Thus, we evaluated the association between county-level social vulnerability and in-hospital mortality and MACE in a national cohort of hospitalized COVID-19 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Several epidemiological studies have extensively characterised MACE during and after COVID-19 [ 7 , 27 , 44 , 45 ]. A recent systematic review of 150 studies with 33,805 patients showed that COVID-19 increased the risk of developing MACE.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have extensively characterised MACE during and after COVID-19 [ 7 , 27 , 44 , 45 ]. A recent systematic review of 150 studies with 33,805 patients showed that COVID-19 increased the risk of developing MACE.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the aggregation level is based on data availability, so there is a boundary issue. Fifth, the unequal distribution of health outcomes might be caused by unobserved sociodemographic and economic characteristics, such as social vulnerability and air quality since these features might affect health outcomes [ 65 , 66 , 67 ]. Future studies examining the associations between social and environmental characteristics and health outcomes are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been applied previously in registry analyses on cardiovascular disease. 19 In analyses separated by sex, the rates of achievement of the following 4 primary outcomes were compared among the 3 race and ethnic groups (with non-Hispanic White as the reference group): rate of prehospital ECG obtained among patients transported by EMS; arrival to ECG within 10 minutes if no prehospital ECG was obtained; arrival to PCI within 90 minutes; and FMC-to-PCI time within 90 minutes for EMStransported patients. Additional analyses compared by race and ethnic groups (again separately in women and men) were the achievement of 4 additional time-to-treatment STEMI metrics: ED length of stay ≤30 minutes; FMC-to-cardiac catheterization laboratory activation within 20 minutes; door-to-fibrinolysis within 30 minutes; and door-in to door-out time within 30 minutes.…”
Section: Osho Et Almentioning
confidence: 99%